2020
DOI: 10.5098/hmt.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Hall and Ion Slip Effects on Ag - Water Based MHD Nanofluid Flow Over a Semi-Infinite Vertical Plate Embedded in a Porous Medium

Abstract: The present work provides an analysis of the Dufour, radiation absorption, Hall and ion slip effects on MHD free convective rotating flow of Agwater based nanofluid past a semi-infinite permeable moving plate with constant heat source. In this regard, metal will be considered as nanoparticles with water as base fluid. Governing nonlinear boundary layer equations and boundary conditions are transformed into a system of nonlinear ordinary coupled differential equations and are solved by perturbation technique. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This came about as a result of their discussion regarding increasing the Hall current parameter estimate on both carbon nanotube velocity profiles. According to Rani et al (2020), they studied the Hall and Iron slip on MHD nanofluid effect on flow over a vertical semiinfinite plate embedded in a porous media. They concluded that an unsteady perimeter has little effect on Casson nanofluid velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This came about as a result of their discussion regarding increasing the Hall current parameter estimate on both carbon nanotube velocity profiles. According to Rani et al (2020), they studied the Hall and Iron slip on MHD nanofluid effect on flow over a vertical semiinfinite plate embedded in a porous media. They concluded that an unsteady perimeter has little effect on Casson nanofluid velocity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Other most recent investigations on Hall and ion-slip impacts are given in References. [32][33][34][35][36][37][38][39][40] As far as we know, the mixed convection flow of Maxwell nanofluid past an extending sheet with Hall and ion-slip impacts has not been thoroughly considered at this point. Along these lines, the goal of the present investigation is to study the Hall and ion-slip effects on mixed convection flow of a Maxwell nanofluid over a permeable extending sheet employing the spectral relaxation method (SRM).…”
Section: Introductionmentioning
confidence: 99%
“…In this view, the Hall effect occurred as a result of the Lorentz force's action. In the case of a conductor, a current is passed and a magnetic field is applied perpendicularly Dharmaiah et al (2020). As a result, the electrical field potential of the system is developed in both directions of the current and the magnetic field.…”
Section: Introductionmentioning
confidence: 99%